Efektivitas Pembelajaran Vlog Berbasis Zoom pada Mata Kuliah Perencanaan Pembelajaran Prodi PAI di IAIN Manado - Pia Nuraripah; Dwi Ratna Sari; Aris Armeth Daud Alkahar; Evi Sri Handayati (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
Zoom-based learning basically results in passive learning between educators and students so they cannot provide positive stimulation in the learning process. However, this is different from zoom-based learning conducted at IAIN Mando which can be used as a reference for inspiration for students that online learning does not result in passive learning. Studies on online learning are very important to do because at this time apart from the influence of Covid-19 where learning must be done online, but also technological developments that make learning possible in the digital era. This paper aims to reveal the effectiveness of zoom-based vlog learning in the Learning Planning course at IAIN Manado, as one of the State Islamic Higher Education Institutions that implements zoom-based vlog learning. This study reveals how effective it is for students after studying online and what are the supporting factors in implementing zoom-based vlog learning in lesson planning courses. This research is a type of qualitative research, and the methods used are interviews, observation and documentation. Interviews were conducted with 8 students as informants, while the interviews used in this study were semi-structured interview techniques where the questions posed followed the flow of the conversation. This research shows that the State Islamic Religious College of IAIN Manado can be an inspirational reference in seeing its effectiveness in the online learning process. This study shows that the effectiveness of zoom-based vlog learning conducted at IAIN Mando in PAI study programs remains active, this activity can be described as providing a positive response stimulus, can develop student creativity. Learning is said to be creative where the learning process involves students, is not centered on the lecturer, provides arguments based on previously prepared material and makes the best use of time. The supporting factors in implementing zoom-based learning in PAI study programs at IAIN Manado are developmental factors and policy factors.